Selective Exposure to Health Information: The Role of Headline Features in the Choice of Health Newsletter Articles. Issue 4 (1st October 2016) - Kim, Hyun Suk; Forquer, Heather; Rusko, Joseph; Hornik, Robert C.; Cappella, Joseph N.
Abstract : This study investigated how content and context features of headlines drive selective exposure when choosing between headlines of a monthly e-mail health newsletter in a naturalistic setting over a period of nine months. Study participants received a monthly e-mail newsletter and could freely open it and click any headline to read the accompanying article. In each e-mail newsletter, nine headlines competed with each other for selection. Textual and visual information of the headlines was content analyzed, and clickstream data on the headlines were collected automatically. The results showed that headlines invited more frequent audience selections when they provided efficacy-signaling information in an imperative voice, when they used a moderate number of negative emotion words, when they presented negative thumbnail images while mentioning cancer or other diseases, and when they were placed higher in position.